2011
DOI: 10.5114/aoms.2011.20617
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing breast elasticity measured by the ultrasound Shear Wave elastography – preliminary results

Abstract: IntroductionMany physiological changes of breast elasticity depend on the age, hormonal status, menstrual cycle and many others. The aim of this study was to evaluate viscoelastic properties of normal breast tissues in a large group of women and to search for factors which play a role in its mechanical properties.Material and methods101 women aged 18-74 years who underwent B-mode sonography and additionally sonoelastography. We measured viscoelasticity in 8 quadrants by a share wave ultrasonic device estimatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 21 publications
3
35
1
2
Order By: Relevance
“…Rzymski et al reported a correlation between age and the elasticity of glandular tissue, and found no correlations with the age of first pregnancy or gravidity and parity [22]. Recently, Wojcinski et al reported significant differences in elasticity values of the breast parenchyma determined in the premenstrual and postmenstrual phases of the menstrual cycle [24].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Rzymski et al reported a correlation between age and the elasticity of glandular tissue, and found no correlations with the age of first pregnancy or gravidity and parity [22]. Recently, Wojcinski et al reported significant differences in elasticity values of the breast parenchyma determined in the premenstrual and postmenstrual phases of the menstrual cycle [24].…”
Section: Discussionmentioning
confidence: 94%
“…We did not encounter no such blind areas in our study group because of the benign features of lesions. Lesion depth and size, breast tissue density, histopathological features of cancer (e.g., necrotic areas, stage), type of cancer (mucinous or medullary) and some benign conditions (e.g., fat necrosis, radial or surgical scars, peri-abscess inflammation) have been suggested to be possible reasons of false SWE features [22,23,26]. In addition, age, menstrual cycle, and hormone profile of the patient, which play roles in metabolism in the breast tissue, have also been suggested to be factors that may affect the elasticity of breast tissue [22,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean values of stiffness of a healthy liver, glandular, and fatty tissue of the breast as measured in healthy volunteers were 4.64 ± 1.18 kPa 17 , 11.3 ± 5.3 kPa, and 9.2 ± 4.5 kPa, respectively 18 . The mean values in the prostate were 4.1 ± 0.8 kPa and 9.9 ± 0.9 kPa in the peripheral and central zones, respectively 10 .…”
mentioning
confidence: 99%
“…The clinical application of shear wave elastography has already been evaluated in the diagnosis of breast cancer, [20][21][22][23] measurement of muscular stiffness, 24 and characterization of thyroid nodules. 25 As with these clinical applications, hepatic elastography is a promising technique for diagnosis of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%